Suitability Analysis and Carrying Capacity of Marine Ecotourism to Beach Recreation and Swimming Tourism at Muara Nauli Beach, Sorkam Sub-district, Central Tapanuli District - Dion Nainggolan; Insaniah Rahimah; Rosmasita Rosmasita; Fitri Ariani (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
Muara Nauli Beach area has a charm in the form of a sloping white sandy beach and is broad enough and the waters aspects are conducive to being a marine ecotourism. This research was conducted in December2019 at Muara Nauli Beach, Sorkam Sub-district, Central Tapanuli District. The purpose of this study is to assess the suitability and carrying capacity of the area in Muara Nauli Beach as a marine tourismdestination. The method using are calculate of tourism suitability index and carrying capacity with geographical information system technology. The data used are primary data and secondary data. Primary data were obtained from field observations and interviews. Whereas secondary data was obtained from related institutions. The results obtained from the tourism suitability index for beach recreation tourism are the